Exploring Extramission: Plato's Intraocular "Fire" Revisited. (December 2019) - Schott, G. D.
The notion that vision results from light rays being emitted by the eyes, extramission, originated over 2, 000 years ago, but was finally disproved by Kepler around 1600. Yet extramission continues to hold sway, not only in much popular thinking but also as some form of explanation for various visual phenomena. It is suggested that extramission today is a concept that concerns not the eyes and optics but gaze and perception.